MENYATUKAN AKAL DAN HATI DALAM PENDIDIKAN ISLAM: STUDI DI RQDT LAMPUNG - Susilawati, Reni; Rizki Ananda (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study purpose to explore the role of integrating intellect ('aql) and heart (qalb) in character formation and the strategies for its implementation in Islamic education practices at Rumah Qur’an Daarut Tarbiyah (RQDT) Lampung. This institution was chosen due to its unique and holistic approach in instilling Islamic values through a balanced focus on both cognitive and spiritual dimensions. A qualitative descriptive method was employed, combining in-depth interviews, participatory observation, and document analysis. Informants included the head of the institution, teachers, and active students at RQDT. The findings reveal that RQDT effectively integrates the intellect through critical and dialogical learning methods, and the heart through practices such as tadabbur (reflection), muhasabah (self-evaluation), spiritual mentoring, and the strengthening of ethical conduct (adab). This integrative process significantly contributes to shaping students who are intellectually intelligent as well as emotionally and spiritually mature. The implications of this study suggest that a value-based educational model integrating intellect and heart can serve as a strategic alternative in addressing moral and spiritual decline in the digital era. The novelty of this research lies in its focus on a non-formal Islamic education institution, an area that remains underexplored academically, particularly regarding Rumah Qur’an institutions that emphasize the integration of intellect and heart in character development strategies.